Multiple sclerosis: Executive dysfunction, task switching and the role of attention. Issue 2 (April 2018) - Clough, M; Foletta, P; Frohman, AN; Sears, D; Ternes, A; White, OB; Fielding, J
Background: It has been suggested that switching ability might not be affected in multiple sclerosis (MS) as previously thought; however, whether this is true under more 'real-world' conditions when asymmetry in task difficulty is present has not been ascertained. Objective: The objective of this paper is to examine the impact of task difficulty asymmetry on task switching ability in MS. Method: An ocular motor (OM) paradigm that interleaves the simple task of looking towards a target (prosaccade, PS) with the cognitively more difficult task of looking away from a target (antisaccade, PS) was used. Two switching conditions: (1) PS switch cost, switching to a simple task from a difficult task (PS switch), relative to performing two simple tasks concurrently (PS repeat); (2) AS switch cost, switching to a difficult task from a simple task (AS switch) relative to performing two difficult tasks concurrently (AS repeat). Forty-five relapsing–remitting MS patients and 30 control individuals were compared. Results: Controls and patients produced a similar magnitude PS switch cost, suggesting that task difficulty asymmetry does not detrimentally impact MS patients when transitioning from a more difficult task to a simpler task. However, MS patients alone found switching from the simpler PS trial to the more difficult AS trial easier (shorter latency and reduced error) than performing two AS trials consecutively (AS switch benefit). Further, MS patients performed significantly more errors than controls when required to repeat the same trial consecutively. Conclusion: MS patients appear to find the maintenance of task-relevant processes difficult not switching per se, with deficits exacerbated under increased attentional demands.